Establishing the stability number descriptor for Fe-N-C fuel cell electrocatalysts - Ku, Yu Ping; Kumar, Kavita; Bonnefont, Antoine; Jiao, Li; Mazzucato, Marco; Durante, Christian; Jaouen, Frédéric; Cherevko, Serhiy (Chemical Science, 2025)
Fe-N-C electrocatalysts demonstrate high potential in catalyzing oxygen reduction reaction (ORR) in polymer electrolyte fuel cells, yet the bottleneck for their application is their moderate stabilities. In our previous work, we discovered a linear correlation between the rates of ORR and Fe dissolution in alkaline media at room temperature, and the stability (S-) number descriptor that reflects this correlation was introduced. On the way toward further generalization and establishment of this descriptor, we investigate the effect of pH, potential, current density, and temperature on the dissolution behavior of various representative Fe-N-C electrocatalysts. It is shown that the S-number concept is also applicable for ORR and Fe dissolution in alkaline electrolytes at 70 °C. It is more challenging to apply the S-number in acidic media, where the S-number is a function of ORR current density. A kinetic model is introduced, showing that the local pH inside the catalyst layer rises significantly with increasing current densities. The pH dependence of the S-number explains the results in acidic electrolytes. Accounting for such a dependence, the S-number descriptor can also benchmark Fe-N-C stability in acidic electrolytes. It is considered that this concept can also be extended to other reactions, allowing more rational activity and stability screening of electrocatalysts.
CRIS-Team Scopus Importer:2025-05-02